Pedagogical Potential of Poetry in Teaching a Foreign Language to Cadets of Departmental University - O. O. Skobeleva (Научный диалог)
The use of poetic works by English authors at foreign language lessons is covered. The use of poetry in the teaching process is assessed from the point of view of formation of communicative and other skills of the cadets of departmental educational institutions. It is shown that the study of literary works not only forms the worldview of students, their independent aesthetic perception of the world through the realization of the author’s idea, but also contributes to the development of practical language skills. The author’s development of studying poetry at the English language lessons in the Law departmental University is presented. The results of the study show the importance of integrated training in a foreign language and literature. It is noted that the analysis of literary works, the idea of which is expressed in poetic form, allows students to develop observation skills, to improve their thinking and also promotes the formation of communicative competence, encourages them to express their views, while memorizing poems improves memory. It is shown that knowing of the cultural heritage, particularly literature, at foreign language lessons, and the introduction of other cultural elements in the teaching material enhance the understanding of the cadets on the facts of social and cultural sphere and contribute to the development of appropriate skills, which indicates the achievement of the teacher’s pedagogical goals.